2021
DOI: 10.1186/s12985-021-01616-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlation of hepatitis E virus antibody in the patients’ serum samples from a tertiary care hospital in Thailand during 2015–2018

Abstract: Background Prevalence and incidence of hepatitis caused by HEV infection are usually higher in developing countries. This study demonstrated the HEV seroprevalence and incidence of HEV infection in patients with clinical hepatitis in a tertiary hospital in Thailand. Methods A laboratory-based cross-sectional study was conducted using 1106 serum samples from patients suspected of HEV infection sent to the Serology laboratory, Siriraj Hospital, for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
0
3
3
Order By: Relevance
“…It is worth noting that there were only 18 pregnant women aged ≤19 years in this study, with the majority of pregnant women aged 20–29 years. The anti-HEV IgM-positive rate was not affected by age in the present study, differing from findings in previous studies [ 19 , 33 ]. Previous studies concerning the prevalence of HEV were primarily performed based on anti-HEV antibodies [ 4 , 19 , 21 , 22 , 24 , 29 , 31 , 33 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that there were only 18 pregnant women aged ≤19 years in this study, with the majority of pregnant women aged 20–29 years. The anti-HEV IgM-positive rate was not affected by age in the present study, differing from findings in previous studies [ 19 , 33 ]. Previous studies concerning the prevalence of HEV were primarily performed based on anti-HEV antibodies [ 4 , 19 , 21 , 22 , 24 , 29 , 31 , 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The anti-HEV IgM-positive rate was not affected by age in the present study, differing from findings in previous studies [ 19 , 33 ]. Previous studies concerning the prevalence of HEV were primarily performed based on anti-HEV antibodies [ 4 , 19 , 21 , 22 , 24 , 29 , 31 , 33 ]. In this study, all pregnant women were also tested for HEV antigen and HEV RNA.…”
Section: Discussioncontrasting
confidence: 99%
“…Serum total bilirubin is a common marker of liver function, and a high level of blood TBB is indicative of liver injury ( 84 ). HEV-infected patients had elevated levels of TBB compared to uninfected ones ( 20 ). In the present study, we found that serum levels of TBB in HEV-infected pregnant rabbits were higher than those in HEV-infected nonpregnant rabbits and uninfected pregnant rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnant women, adverse effects of HEV-1 infection include vertical virus transmission of >30%, preterm delivery, miscarriage, stillbirth (an estimate of 3,000 cases annually), and fulminant hepatic failure (FHF), with a mortality rate of up to 30% ( 2 , 13 17 ). Recent reports from several countries, including Nigeria ( 18 ), Senegal ( 19 ), Thailand ( 20 ), Egypt ( 21 ), and Argentina ( 22 ), showed that HEV infections in pregnant women continue to be a more significant clinical problem than in nonpregnant women and immunocompetent individuals. Among the hepatotropic viruses, the high mortality in pregnant women is unique to HEV, and therefore, there is a critical need for an appropriate animal model to delineate the underlying mechanisms of HEV-induced adverse outcomes during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent years showed a decreasing trend: 49.01% in 2016, 37.68% in 2017, and 26.04% in 2018 in the same population. It is notable that the seroprevalence of HEV demonstrated an increase with advancing age groups [ 31 ]. The decline in the seroprevalence of both HAV and HEV might be due to improved hygiene in Thailand.…”
Section: Discussionmentioning
confidence: 99%